Fibroma of Buccal Mucosa: Case Report and Literature Review - Elrahawy, Khaled Mohamed Afify; Nagy, Ahmed Ismail; El-Swilem, Rayan Okla (European Scientific Journal, ESJ, 2017)
The fibroma, also referred to as irritation fibroma, is by far the most common of the oral fibrous tumorlike growths. While the terminology implies a benign neoplasm, most if not all fibromas represent reactive focal fibrous hyperplasia due to trauma or local irritation. Although the term focal fibrous hyperplasia more accurately describes the clinical appearance and pathogenesis of this entity, it is not commonly used. We present a case report of oral fibroma in the left side of the buccal mucosa in 50 years old Saudi patient.